Migration news in Turkey and the language of emotion - Uzun, Cemile (IGI Global, 2024)
Analyzing the emotional tone used in migration-related news articles is important for revealing how lan-guage patterns employed in news texts infl;uence society. This study aimed to determine which emotional tones are used in migration-related newspaper articles in Turkey. To achieve this goal, the emotional tone of migration-related news articles from four newspapers published in Turkey-Hürriyet, Posta, Sabah, and Cumhuriyet-was examined. Tokuhisa, Inui, and Matsumoto"s emotional tone analysis was employed to classify the emotional tone of the news articles. From the obtained data, it was determined which emotional tone predominates in migration-related news articles in these newspapers. This analysis is crucial for uncovering how emotional tone is utilized in migration-related news articles and identifying the factors that infl;uence the emotional tone used. © 2024 by IGI Global. All rights reserved.